Method for Mueller matrix acquisition based on a division-of-aperture simultaneous polarimetric imaging technique. (March 2019) - Ju, Haijuan; Ren, Liyong; Liang, Jian; Qu, Enshi; Bai, Zhaofeng
Highlights: Based on an aperture-divided polarimetric imaging technique, a new method for Mueller matrix acquisition is proposed, which has the advantages of time-saving and simple in computation. Compared to traditional methods where obtaining all 16 elements of Mueller matrix needs to measure 16 times, our method just needs to change the SOP of the incoming light 4 times. A maximal measurement mean error of Mueller matrix element is obtained to be 0.033, which verifies the effectiveness of the method. Abstract: The Mueller matrix is an important parameter in the field of polarization optics, and how to measure it efficiently and accurately becomes considerably significant for its practical applications. In this paper, for the first time to our knowledge, we propose a new method for Mueller matrix acquisition based on a division-of-aperture simultaneous polarimetric imaging technique. Different from the traditional method where, for obtaining the 16 elements of the Mueller matrix, a 16-times-measurement must be conducted by jointly changing the states of polarization (SOPs) of the input and output lights, while in our method it is enough by just changing the SOPs of the input light 4 times. This time-saving and easy-calculating feature is owing to our specific polarimetric camera, where a full-Stokes vector is obtained easily since 3 linear SOPs (0°, 45°, 90°) and 1 circular SOP can be recorded simultaneously by spatially sharing the same detector. To simply verify the effectiveness of our method, a specific polarization device patched by 8 sub-polarizers is chosen as the sample to be measured. Experimental results show that they are consistent with the theoretical results, both in the Mueller matrix and the corresponding images. We predict that this method for Mueller matrix acquisition can get wide potential applications for rapid identifications in biomedicine and material science.